Songs of the reggaetón and social skills in the perspective of adolescents of Educational Institutions of the city of Puno - Chambi, Edwin (2019)
This research aims to analyze the relationship of similarities and differences on the opinion of reggaetón songs and social skills expressed in the perspective of adolescents of both genders of the city of Puno - 2017. The research is comparative correlation, the technique that was applied was the survey, the sample was constituted by 201 students of the fifth grade of secondary of the Institutions Glorioso San Carlos and Santa Rosa de Puno. Considering that today adolescents are influenced by new musical trends such as reggaeton, which in their lyrics have messages of double meaning, which contributes to the loss of values ​​that is being presented today, where the adolescent interprets and takes as a life form. Throughout this research work has come to the relationship of similarities and differences on the opinion of reggaetón songs and social skills expressed in the perspective of adolescents of both genders of the city of Puno - 2017 is significant, in this way the hypothesis proposed in the research work is accepted.